2012
DOI: 10.2147/ppa.s32745
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and type 2 diabetes mellitus: what do we know, and what we can do?

Abstract: Diabetes mellitus (DM) is a pandemic and chronic metabolic disorder with substantial morbidity and mortality. In addition, osteoporosis (OP) is a silent disease with a harmful impact on morbidity and mortality. Therefore, this systematic review focuses on the relationship between OP and type 2 diabetes mellitus (T2DM). Systematic reviews of full-length articles published in English from January 1950 to October 2010 were identified in PubMed and other available electronic databases on the Universiti Sains Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 153 publications
7
69
3
2
Order By: Relevance
“…Many studies investigated the relationship between T2DM and bone metabolism, but their results were inconsistent. For patients with T2DM, some authors have reported increased BMD, others have reported decreased BMD, and some have reported unaltered BMD 16 . Th e aim of this study was to investigate the relationship between components of the metabolic syndrome, central adiposity and hyperinsulinemia, as well as infl ammation markers with vertebral and femoral BMD and bone turnover markers in postmenopausal women with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigated the relationship between T2DM and bone metabolism, but their results were inconsistent. For patients with T2DM, some authors have reported increased BMD, others have reported decreased BMD, and some have reported unaltered BMD 16 . Th e aim of this study was to investigate the relationship between components of the metabolic syndrome, central adiposity and hyperinsulinemia, as well as infl ammation markers with vertebral and femoral BMD and bone turnover markers in postmenopausal women with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between type 2 diabetes and osteoporosis has been broadly studied, some details remain controversial [9]. Type 2 diabetes could influence bone metabolism through many mechanisms [10]. Studies regarding the association between Type 2 diabetes and bone quality showed different results: some studies reported that diabetes increased BMD [11], while others reported that it either decreased [12] or did not affect the BMD in patients with osteoporosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM), although considered a disease of glucose regulation, is associated with wide-ranging derangement of metabolic and vascular homeostasis [3]. Worldwide approximately 382 million people have diabetes, 3.2 million of whom are in the UK, of which 90% have type 2 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, obesity and a sedentary lifestyle can affect balance, gait and co-ordination. Any combination of these can lead to an increased falls risk [3,10,11]. However, even in studies that controlled for fall frequency, T2DM remained independently associated with higher fragility fracture risk [6].…”
Section: Introductionmentioning
confidence: 99%